The antecedents and consequences of electronic invoice in China from a tax perspective / Qi Yu Lan - Qi , Yu Lan (2021)
The purpose of this study is to examine the factors that affect the adoption of electronic invoice and in return the consequences of these factors on tax compliance process efficiency of companies in China. A questionnaire survey was distributed to 276 users who adopted electronic invoice and partial least squares regression was used to analyze the data. This study found that perceived benefits and trust in e-government had a positive influence on the adoption of electronic invoice. Furthermore, we also found that the adoption of electronic invoice have a positive impact on the efficiency of the tax compliance process. Moreover, the factors affecting adoption of electronic invoice can have a mediating effect between adoption and tax compliance process efficiency. This study has some limitations because it only explores these influencing factors on companies that has adopted electronic invoice. Future research will be carried out to distinguish between adopters and non-adopters. The results of this study can guide tax authorities and other electronic invoice suppliers to promote the adoption of electronic invoice. This study contributes to the electronic adoption literature by examining antecedents that have consequences on tax compliance processes efficiency.